Linking Islamic Corporate Social Responsibility, Sharia Governance Practices, and Earnings Management in the Islamic Banks - Muhfiatun, Muhfiatun; Prasojo, Prasojo; Wijayanti, Dwi Marlina; Fitrijanti, Tettet (Jurnal Dinamika Akuntansi dan Bisnis, 2022)
This paper examines the relationship between corporate social responsibility, sharia governance, and earning management in the Islamic bank industry sector. This study uses secondary data, which is analyzed using a regression panel with a fixed-effect model. Samples were obtained from 48 Islamic banks in 16 countries from 2009 to 2018. The sample criteria in this study are the banks that disclose their zakat payments in their annual reports. The empirical results prove that CSR and SSB expertise contributes significantly to reducing earnings management practices, while SSB size is not significantly influencing earnings management practices. The contribution to policymakers in developing CSR instruments following Sharia principles; Islamic bank manager aligns CSR intentions based on the concept of monotheism to enrich the literature review on CSR, sharia governance, and earning quality.